2021
DOI: 10.1111/pbi.13689
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic view on lodging resistance in rye and wheat: a multiscale comparative study

Abstract: Summary The development of crop varieties that are resistant to lodging is a top priority for breeding programmes. Herein, we characterize the rye mutant ´Stabilstroh’ (‘stable straw’) possessing an exceptional combination of high lodging resistance, tall posture and high biomass production. Nuclear magnetic resonance imaging displayed the 3‐dimensional assembly of vascular bundles in stem. A higher number of vascular bundles and a higher degree of their incline were the features of lodging‐resistant versus lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 118 publications
(146 reference statements)
0
8
0
1
Order By: Relevance
“…High yielding cereal varieties need to develop stems with a high degree of mechanical strength to avoid wind‐induced collapse (referred to as ‘lodging’). MRI‐based investigation of the structure of both the wheat and the rye stem has shown that lodging resistance is associated with both a high number of vascular bundles and a greater degree of their incline (Muszynska et al ., 2021).…”
Section: Mri As a Noninvasive Approachmentioning
confidence: 99%
“…High yielding cereal varieties need to develop stems with a high degree of mechanical strength to avoid wind‐induced collapse (referred to as ‘lodging’). MRI‐based investigation of the structure of both the wheat and the rye stem has shown that lodging resistance is associated with both a high number of vascular bundles and a greater degree of their incline (Muszynska et al ., 2021).…”
Section: Mri As a Noninvasive Approachmentioning
confidence: 99%
“…Quantitative and histochemical analysis further indicated that wounding increased lignin accumulation and activity of enzymes involved in lignin synthesis, which resulted in increased mechanical strength and the lodging resistance index in the main stem. Varieties with higher lodging resistance have elevated levels of lignin, xylan, zinc, and silicon (Muszynska et al., 2021). Somewhat surprisingly, genes associated with lignin biosynthesis were generally downregulated in the later time points of our 2‐h time course, while lignin content has been reported to be increased after mechanostimulation in, e.g., Brachypodium, Arabidopsis, and Papaya (Brenya et al., 2020; Gladala‐Kostarz et al., 2020; Porter et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The number of vascular bundles is one of the important factors affecting the mechanical properties of stems [ 89 , 90 ]. Muszynska et al [ 91 ] compared extreme lodging rye mutants and found that the lodging-resistant rye strain “MS135” was taller, with more tiller, had higher biomass production and heavier stalks with significantly more outer vascular bundles, and had a higher proportion of sclerenchyma cells. Recent research has shown that vascular bundles and surrounding leaf sheaths also contribute significantly to lodging resistance [ 92 , 93 , 94 , 95 ].…”
Section: Vascular Bundles Development In Establishing Ideal Plant Arc...mentioning
confidence: 99%